Proactive Risk Assessments and the Continuity of Business Principles: Perspectives on This Novel, Combined Approach to Develop Guidance for the Permitted Movement of Agricultural Products during a Foot-and-Mouth Disease Outbreak in the United States - Goldsmith, Timothy J.; Culhane, Marie Rene; Sampedro, Fernando; Cardona, Carol J. (Frontiers in Veterinary Science, 2017)
Animal diseases such as foot-and-mouth disease (FMD) have the potential to severely impact food animal production systems. Paradoxically, the collateral damage associated with the outbreak response may create a larger threat to the food supply, social stability, and economic viability of rural communities than the disease itself. When FMD occurs in domestic animals, most developed countries will implement strict movement controls in the area surrounding the infected farm(s). Historically, stopping all animal movements has been considered one of the most effective ways to control FMD and stop disease spread. However, stopping all movements in an area comes at a cost, as there are often uninfected herds and flocks within the control area. The inability to harvest uninfected animals and move their products to processing interrupts the food supply chain and has the potential to result in an enormous waste of safe, nutritious animal products and create animal welfare situations. In addition, these adverse effects may negatively impact agriculture businesses and the related economy. Effective disease control measures and the security of the food supply thus require a balanced approach based on science and practicality. Evaluating the risks associated with the movement of live animals and products before an outbreak happens provides valuable insights for risk management plans. These plans can optimize animal and product movements while preventing disease spread. Food security benefits from emergency response plans that both control the disease and keep our food system functional.